The systemic inflammation response index as a significant predictor of short-term adverse outcomes in acute decompensated heart failure patients: a cohort study from Southern China - Lin Xie; Qun Wang; Hengcheng Lu; Maobin Kuang; Maobin Kuang; Maobin Kuang; Shiming He; Shiming He; Shiming He; Guobo Xie; Guotai Sheng; Shuhua Zhang; et al. (Frontiers in Endocrinology)
ObjectiveThe deterioration of acute decompensated heart failure (ADHF) is associated with abnormal activation of inflammatory pathways. This study aims to evaluate the impact and predictive value of a novel inflammatory marker, the systemic inflammation response index (SIRI), on short-term adverse outcomes in ADHF patients.MethodsThis retrospective cohort study included 1,448 ADHF patients from Jiangxi Provincial People’s Hospital between 2019-2022. SIRI was calculated using the formula: (neutrophil count × monocyte count)/lymphocyte count. In the correlation analysis, the study outcome was the 30-day mortality in patients with ADHF. Cox regression analysis and receiver operating characteristic curves were employed to investigate the risk assessment and predictive value of the SIRI for 30-day mortality in ADHF patients. Finally, we also exploratively assessed the mediation effect of nutritional factors (albumin: Alb, total cholesterol: TC, and lymphocyte count) on the association between SIRI and 30-day mortality in ADHF patients.ResultsDuring the 30-day follow-up, 53 deaths were recorded. Mortality rates across SIRI tertiles were 0.62%, 2.07%, and 8.28%, respectively. There was a significant linear positive correlation between SIRI and 30-day mortality in ADHF patients (HR: 1.21; P for non-linearity = 0.113). Additionally, compared to ADHF patients with low SIRI, those with high SIRI had a 685% increased risk of 30-day mortality (HR: 7.85). Furthermore, receiver operating characteristic curve analysis demonstrated that SIRI significantly improved the predictive value for 30-day mortality in ADHF patients compared to neutrophil count, monocyte count, and lymphocyte count alone (AUC: neutrophil count 0.7633, monocyte count 0.6835, lymphocyte count 0.7356, SIRI 0.8237; all DeLong P<0.05). Mediation analyses indicated that, except for lymphocyte count, both Alb and TC had significant indirect effects on the SIRI-related 30-day mortality in ADHF patients; Specifically, Alb accounted for approximately 24.46% of the mediation effect, while TC accounted for approximately 13.35%.ConclusionThis cohort study based on a Southern Chinese population demonstrates a significant linear positive correlation between SIRI and 30-day mortality in ADHF patients, highlighting its substantial predictive value. Incorporating SIRI into the monitoring regimen of ADHF patients may be crucial for preventing further disease progression.